Concise Review: Advanced Cell Culture Models for Diamond Blackfan Anemia and Other Erythroid Disorders. (5th December 2017) - Migliaccio, Anna Rita; Varricchio, Lilian
Abstract : In vitro surrogate models of human erythropoiesis made many contributions to our understanding of the extrinsic and intrinsic regulation of this process in vivo and how they are altered in erythroid disorders. In the past, variability among the levels of hemoglobin F produced by adult erythroblasts generated in vitro by different laboratories identified stage of maturation, fetal bovine serum, and accessory cells as "confounding factors, " that is, parameters intrinsically wired in the experimental approach that bias the results observed. The discovery of these factors facilitated the identification of drugs that accelerate terminal maturation or activate specific signaling pathways for the treatment of hemoglobinopathies. It also inspired studies to understand how erythropoiesis is regulated by macrophages present in the erythroid islands. Recent cell culture advances have greatly increased the number of human erythroid cells that can be generated in vitro and are used as experimental models to study diseases, such as Diamond Blackfan Anemia, which were previously poorly amenable to investigation. However, in addition to the confounding factors already identified, improvement in the culture models has introduced novel confounding factors, such as possible interactions between signaling from cKIT, the receptor for stem cell factor, and from the glucocorticoid receptor, the cell proliferation potential and the clinical state of the patients. This review will illustrate these new confounding factors and discuss their clinical translation potential to improve our understanding of Diamond Blackfan Anemia and other erythroid disorders. Abstract : Modelling the erythroid island in vitro. In solution, erythroblasts and macrophages tend to form associations which are resistant to modest physical stresses such as those established when the cells pass through a cytofluorimeter flow or during the centrifugation step necessary to prepare cytosmear [19, 20]. The mechanisms which regulate this in vitro association are currently under investigation and may shed light on the formation of the erythroid islands in the bone marrow. This representative confocal microscopy image of a cytocentrifuged preparation depicts interactions occurring between human erythroid cells and macrophages generated in culture. The cells were obtained from a polycythemia vera patient cultured for 10 days under the same conditions used to expand those presented in the Movie and were stained with antibodies for erythroid macrophage protein (EMP) [21] (green signal) and Glycophorin A (red signal). Macrophages express robust levels of EMP while erythroblasts (identified by the Glycophorin A staining) do not. Nuclei were counterstained with DAPI. Original magnification ×1, 500. The representative scale bar corresponds to 10µm. See also Supporting Information Movie S1 and [92].